Lung inflammatory and oxidative alterations after exogenous surfactant therapy fortified with budesonide in rabbit model of meconium aspiration syndrome - Mikolka, P; Kopincová, J; Košútová, P; Čierny, D; Čalkovská, A; Mokrá, D (Physiological research, 2016)
Meconium aspiration syndrome (MAS) triggers inflammatory and oxidative pathways which can inactivate both pulmonary surfactant and therapeutically given exogenous surfactant. Glucocorticoid budesonide added to exogenous surfactant can inhibit inflammation and thereby enhance treatment efficacy. Neonatal meconium (25 mg/ml, 4 ml/kg) was administered intratracheally (i.t.) to rabbits. When the MAS model was prepared, animals were treated with budesonide i.t. (Pulmicort, 0.25 mg/kg, M+B); with surfactant lung lavage (Curosurf®, 10 ml/kg, 5 mg phospholipids/ml, M+S) followed by undiluted Curosurf® i.t. (100 mg phospholipids/kg); with combination of budesonide and surfactant (M+S+B); or were untreated (M); or served as controls with saline i.t. instead of meconium (C). Animals were oxygen-ventilated for additional 5 h. Cell counts in the blood and bronchoalveolar lavage fluid (BAL), lung edema formation (wet/dry weight ratio), oxidative damage of lipids/ proteins and inflammatory expression profiles (IL-2, IL-6, IL-13, TNF-alpha) in the lung homogenate and plasma were determined. Combined surfactant+budesonide therapy was the most effective in reduction of neutrophil counts in BAL, oxidative damage, levels and mRNA expression of cytokines in the lung, and lung edema formation compared to untreated animals. Curosurf fortified with budesonide mitigated lung inflammation and oxidative modifications what indicate the perspectives of this treatment combination for MAS therapy.
Keywords: Oxidative Stress; Pulmonary Surfactants; oxidační stres; antiflogistika; Female; peroxidace lipidů; budesonid; zvířata; Meconium Aspiration Syndrome; ženské pohlaví; Male; Rabbits; plicní surfaktanty; králíci; Anti-Inflammatory Agents; Budesonide; Animals; Inflammation Mediators; mužské pohlaví; kombinovaná farmakoterapie; mediátory zánětu; syndrom aspirace mekonia; Disease Models, Animal; Lipid Peroxidation; Drug Therapy, Combination; modely nemocí na zvířatech